2013
DOI: 10.1158/0008-5472.can-13-0869
|View full text |Cite
|
Sign up to set email alerts
|

C1GALT1 Enhances Proliferation of Hepatocellular Carcinoma Cells via Modulating MET Glycosylation and Dimerization

Abstract: Altered glycosylation is a hallmark of cancer. The core 1 b1,3-galactosyltransferase (C1GALT1) controls the formation of mucin-type O-glycans, far overlooked and underestimated in cancer. Here, we report that C1GALT1 mRNA and protein are frequently overexpressed in hepatocellular carcinoma tumors compared with nontumor liver tissues, where it correlates with advanced tumor stage, metastasis, and poor survival. Enforced expression of C1GALT1 was sufficient to enhance cell proliferation, whereas RNA interference… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 45 publications
3
93
0
Order By: Relevance
“…C1GALT1 has been shown to regulate angiogenesis, thrombopoiesis, and kidney development. 17,18 Moreover, we recently reported that C1GALT1 alters O-glycans on hepatocyte growth factor receptor, also known as MET, and enhances MET dimerization in hepatocellular carcinoma 19 ; modifies O-glycans on fibroblast growth factor receptor 2 and its downstream signaling involved in colorectal cancer malignant phenotypes 20 ; and enhances breast cancer malignant progression by modulating O-glycans on Mucin (MUC) 1 and promoting MUC1-C/Acatenin signaling pathway. 21 Although C1GALT1 and mucintype O-glycosylation have been shown to play crucial roles in a variety of biologic functions, the roles of C1GALT1 in ovarian cancer remain unclear.…”
mentioning
confidence: 99%
“…C1GALT1 has been shown to regulate angiogenesis, thrombopoiesis, and kidney development. 17,18 Moreover, we recently reported that C1GALT1 alters O-glycans on hepatocyte growth factor receptor, also known as MET, and enhances MET dimerization in hepatocellular carcinoma 19 ; modifies O-glycans on fibroblast growth factor receptor 2 and its downstream signaling involved in colorectal cancer malignant phenotypes 20 ; and enhances breast cancer malignant progression by modulating O-glycans on Mucin (MUC) 1 and promoting MUC1-C/Acatenin signaling pathway. 21 Although C1GALT1 and mucintype O-glycosylation have been shown to play crucial roles in a variety of biologic functions, the roles of C1GALT1 in ovarian cancer remain unclear.…”
mentioning
confidence: 99%
“…The alteration of O-glycans attached to the epidermal growth factor receptor (EGFR) mediated by the down-regulation of GALNT2 plays a critical role in the malignant phenotype of HCC cells (22). Moreover, overexpression of core 1␤-1,3-galactosyltransferase activates hepatocyte growth factor signaling in hepatocellular carcinoma (23). Therefore, understanding the roles of O-glycosylation in hepatocellular carcinoma may provide novel insights into the pathogenesis of hepatocellular carcinoma.…”
mentioning
confidence: 99%
“…N-glycans and related genes including MGAT5 are also known to affect growth factor receptor signaling (Matsumoto et al 2008 ;Park et al 2012 ; also reviewed in Lau and Dennis 2008 ). The glycan-related genes involved in O-glycan synthesis such as GALNT14 , GALNT2 , and C1GALT1 on death receptors, and growth factor receptors such as c-Met and EGFR have recently been suggested to affect cancer cell apoptosis and proliferation ( Wagner et al 2007 ;Wu et al 2011Wu et al , 2013. Altered expression of these glycans may well play significant roles during the course of carcinogenesis.…”
Section: Biological Functions Of Normal Glycansmentioning
confidence: 99%